Asthma at the interface: bridging the gap between general practice and a district general hospital. Issue 4 (April 1994) - Charlton, I; Antoniou, A G; Atkinson, J; Campbell, M J; Chapman, E; Mackintosh, T; Schapira, D
Abstract : A clinic supervised by a nurse, using principles originally developed in general practice, was established in the paediatric department of a district general hospital. A randomised controlled study was conducted comparing children admitted with asthma or attending outpatients who were given a patient education programme and self management plan (intervention group) with a control group. The study comprised 91 patients aged 3-14 years admitted for asthma or attending a hospital outpatient department from November 1989 to November 1990. Seventy seven patients completed the study and kept diaries for a median of 283 days. Patients in the intervention group had significantly less restriction of activity (95% confidence interval (CI) -0.27 to -0.01) and fewer episodes of peak flow below 30% of best (95% CI 0.03 to 1.17). Patients in the intervention group were more likely to make the correct response to an acute exacerbation of their asthma than the control group (71% v 47%, 95% CI 9.51 to 39.1). The intervention group had fewer school absences and fewer home visits by a general practitioner. There was an increase in the readmission rate for the intervention group. A subgroup of patients who self managed by doubling their use of inhaled steroids during an exacerbation performed better than those patients who only increased their bronchodilator or were managed on salbutamol or sodium cromoglycate alone. Improvements in patient follow up and the structure of the self management plans used, particularly changing the peak flow level at which inhaled steroids are doubled, may further improve the outcome of patients attending the asthma clinic.